Unseen Cinema - Inverted Narratives: New Directions in Storytelling Early American Avant-Garde Film 1894-1941 - Beheim, Eric; Blitzstein, Marc; Sauer, Rodney (image Entertainment, 2005)
Early directors D.W. Griffith and Lois Weber develop the radical language of cinema narrative through audience-friendly melodramas made for nickelodeon theaters. Experimental fantasies are depicted in such independent productions as "Moonland" (c. 1926), "Lullaby" (1929), and "The Bridge" (1929-30). Depression era films by socially-conscious filmmakers reshape drama as demonstrated in Josef Berne's brooding "Black Dawn" (1933) and Strand and Hurwitz's biting "Native Land" (1937-41): each pictures a raw reality. Parody and satire find their mark in Theodore Huff's "Little Geezer" (1932) and Barlow, Hay and Le Roy's "Even as You and I" (1937). David Bradley's "Sredni Vashtar" by Saki (1940-43) boasts an inadvertent post-modern attitude. [Cover]
Keywords: DVD-Video